Penerapan Self Generated Analogy sebagai Upaya Meningkatkan Kemampuan Berpikir Kreatif Siswa SMA pada Materi Sistem Peredaran Darah - Islamiati, Fiqa; Kusnadi, Kusnadi; Suhara, Suhara (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
The aim of the reseatch want to analyze the improvement of students’ creative thinking ability in blood circulation system by applying self generated analogy. This research was done in a Public High School in Cimahi and was applied to two classes, the experiment class with 36 students and control class with 31 students.The method used for this research was quasi experimental. The samplewas selected by purposive technique. The data werecollectedby doing creative thinking ability test in form of essay, students’ questionnaire, and classroom observation. The difference of creative thinking ability was reviewed form the result of the test given before and after treatment, and the improvement was seen using N-gain. The test result was compared by doing a statistical test using a software program, SPSS statistic 16.The result of the research shows that there is a significant difference in the creative thinking ability between the treatment and control group class, with a high improvement in the treatment class and medium improvement in control class. The average of posttest in the self generated analogy class is 83,2higher than the control class, which is 65,9. The N-gain result of creative thinking ability in the treatment class is around 0,59 (high category) whereas the control class is around 0,28 (low category). It shows that self generated analogy improves students’ creative thinking ability. The questionnaire showpositive response from students that self generated analogy is able to improve students creative thinking abilityin teaching circulation system.